Effect of pandemic on performance of contracts and remedies to the cases of breach: Looking into legal responses - Dubey, Maitreyee; Dimri, Shikha (Linguistics and Culture Review, 2021)
There would hardly be any walk of life which has gone unaffected by the COVID-19 pandemic. Its effect on the performance of contracts has also attracted legal questions and practical balancing of interests. In deciding whether a sum stipulated to be paid in case of breach of contract is liquidated damages or penalty to secure performance of the contract, intention of party is an important factor in determining but not always controlling one. Substantially, remedies are given by actions in cases of performance of contracts. The nature of the contract determines the kind of remedies. The article demonstrates the structure of damages, penalty-default theory as derived from Hadley v. Baxendale. It also analyses the effects brought in by the Covid-19 pandemic over the award of damages. By this article, the authors aim to analyze the two most crucial aspects of the Indian Contract Act ie. Performace, frustration, and award of damages. The article attempts to scrutinize the dimensions and ways in which these words can be interpreted and applied. In this paper, the author will rely on critical and comparative analysis. For certain empirical demands of the topic, already published data and information will be relied on and acknowledged.